Gentleman in Moscow: A Novel - Towles, Amor (Newyork Viking Penguin, 2016)
The mega-bestseller with more than 2 million readers, soon to be a major television seriesFrom the #1 New York Times-bestselling author of The Lincoln Highway and Rules of Civility, a beautifully transporting novel about a man who is ordered to spend the rest of his life inside a luxury hotel In 1922, Count Alexander Rostov is deemed an unrepentant aristocrat by a Bolshevik tribunal, and is sentenced to house arrest in the Metropol, a grand hotel across the street from the Kremlin. Rostov, an indomitable man of erudition and wit, has never worked a day in his life, and must now live in an attic room while some of the most tumultuous decades in Russian history are unfolding outside the hotel$1 (Bs doors. Unexpectedly, his reduced circumstances provide him entry into a much larger world of emotional discovery. Brimming with humor, a glittering cast of characters, and one beautifully rendered scene after another, this singular novel casts a spell as it relates the count$1 (Bs endeavor to gain a deeper understanding of what it means to be a man of purpose.s